Use of Genomic Tools to Improve Cattle Health in the Context of Infectious Diseases - Raszek, Mikolaj M.; Guan, Le L.; Plastow, Graham S. (Frontiers in Genetics, 2016)
Although infectious diseases impose a heavy economic burden on the cattle industry, the etiology of many disorders that affect livestock is not fully elucidated, and effective countermeasures are often lacking. The main tools available until now have been vaccines, antibiotics and antiparasitic drugs. Although these have been very successful in some cases, the appearance of parasite and microbial resistance to these treatments is a cause of concern. This review describes the rapid gains achieved to track disease progression, identify the pathogens involved, and map pathogen interactions with the host. Next-generation sequencing provides important opportunities to tackle problems associated with pathogenic illnesses. Use of novel genomic tools subsequently aids in treatment development, as well as successful creation of breeding programs aimed towards less susceptible livestock. These may be important tools for mitigating the long term effects of combating infection and helping reduce the reliance on antibiotic treatment.